Orthonormal Decomposition of Third Rank Tensors and Applications - Dinckal, Cigdem; Dinçkal, Çiğdem (int Assoc Engineers-iaeng, 2013)
A new procedure for representation of third rank tensors in terms of its orthonormal irreducible decomposed parts, namely as irreducible decomposition is presented. Orthonormal tensor basis method is developed by using the results of existing theory in the literature. As an example to third rank tensors, piezoelectricity tensor is decomposed by each method and results of this decomposition methods are compared for this tensor in hexagonal symmetry. As a result of comparison process, it is stated that the results for new method and other one are consistent and each decomposed parts have physical meaning. Moreover, the norm concept of piezoelectricity tensor is used to study the piezoelectric effect of some materials. It is also shown that one can determine in which material the piezoelectric effect is stronger by using the norm for different materials with the same symmetries.
Orthonormal decomposition of third rank tensors and applications
Keywords: Third Rank Tensor; Piezoelectricity Tensor; Irreducible Decomposition Method; Orthonormal Tensor Basis Method